Cognitive reappraisal and need to belong predict prosociality in Mexican‐origin adolescents. Issue 2 (2nd November 2022) - Hodge, Ryan T.; Guyer, Amanda E.; Carlo, Gustavo; Hastings, Paul D.
Abstract: This 2‐year longitudinal study examined Mexican‐origin adolescents' need to belong and cognitive reappraisal as predictors of multiple forms of prosocial behavior (i.e., general, emotional, and public prosocial behaviors). Prosocial behaviors, which are actions intended to benefit others, are hallmarks of social proficiency in adolescence and are influenced by intrapersonal abilities and motivations that typically develop during adolescence. Yet, few studies of Mexican‐origin or other U.S. Latinx youths have examined whether such individual difference characteristics, specifically social motivation and emotion regulation skills, support prosocial behavior. In a sample of 229 Mexican‐origin youth ( M age  = 17.18 years,   SD  = .42, 110 girls), need to belong, cognitive reappraisal, and general prosocial behaviors were assessed at ages 17 and 19. Emotional and public forms of prosociality also were assessed at age 19. Cognitive reappraisal was positively associated with concurrent general prosociality at age 17, whereas need to belong was positively associated with concurrent public prosociality at age 19. Moderation analyses revealed that general and emotional types of prosocial behaviors at age 19 were lowest for youth with both lower need to belong and less use of cognitive reappraisal at 19 years. Greater cognitive reappraisal skills and need to belong may reflect distinct motivations for engaging in varying forms of prosocial behavior in late adolescence.